PENGARUH RETAIL MIX TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI DM BARU SWALAYAN BANTUL - Analde, Iddam Restu; Sukardi, Sukardi (Universitas Ahmad Dahlan, 2016)
This study aims to determine (1) whether there is a retail effect mix (Product Diversity, Store Location, Pricing, Consumer Services, Store Design and Display, and Communication Mix) on purchasing decisions consumers in DM Baru Swalayan Bantul both partially and simultaneously. The object in this study is DM Baru Swalayan Bantul. This research was conducted by distributing questionnaires to 100 respondents are DM Baru Swalayan consumers who have shopped at least 2x (twice) in March and April. Analyzer used to measure the effect of Retail Mix on purchasing decisions is linear regression analysis multiple. Based on the results of the research variable Product Diversity, Store Location, Pricing, Consumer Services, Store Design and Display, and Communication Mix effect simultaneously, this is indicated by the value significance less than 0.05 is 0,000. While the variables are partial effect is the customer service variable (X4) with value significance 0.004 <0.05 and the Communication Mix variable (X6) with values significance of 0.009 < 0.05.